Screening for Novel Beneficial Environmental Bacteria for an Antagonism-Based Erwinia amylovora Biological Control - Guillermo Esteban-Herrero; Belén Álvarez; Ricardo D. Santander; Elena G. Biosca (Microorganisms, 2023)
Erwinia amylovora, the bacterial species responsible for fire blight, causes major economic losses in pome fruit crops worldwide. Chemical control is not always effective and poses a serious threat to the environment and human health. Social demands for eco-sustainable and safe control methods make it necessary to search for new biocontrol strategies such as those based on antagonists. A bacterial collection from different fire blight-free Mediterranean environments was tested for antagonistic activity against Spanish strains of E. amylovora. Antagonistic assays were carried out in vitro in culture medium and ex vivo in immature loquat and pear fruits. Results revealed that 12% of the 82 bacterial isolates tested were able to inhibit the growth of several strains of the pathogen. Some of the isolates also maintained their antagonistic activity even after chloroform inactivation. Selected isolates were further tested ex vivo, with several of them being able to delay and/or reduce fire blight symptom severity in both loquats and pears and having activity against some E. amylovora strains. The isolates showing the best antagonism also produced different hydrolases linked to biocontrol (protease, lipase, amylase, and/or DNAse) and were able to fix molecular nitrogen. Based on this additional characterization, four biocontrol strain candidates were further selected and identified using MALDI-TOF MS. Three of them were Gram-positive bacteria belonging to Bacillus and Paenarthrobacter genera, and the fourth was a Pseudomonas strain. Results provide promising prospects for an improvement in the biological control strategies against fire blight disease.